Removal of per- and polyfluoroalkyl substances from aqueous media using synthesized silver nanocomposite-activated carbons - Omo-Okoro, Patricia N; Curtis, Christopher J; Marco, Ana Miralles; Melymuk, Lisa; Okonkwo, Jonathan O (Journal of environmental health science & engineering, 2021)
PURPOSE: Per- and polyfluoroalkyl substances (PFAS) have been found to be widespread, extremely persistent and bioaccumulative with toxicity tendencies. Pre-synthesized nanocomposite-activated carbons, referred to, as physically activated maize tassel silver (PAMTAg) and chemically activated maize tassel silver (CAMTAg) were utilized in the present study. They were used for the removal of 10 PFAS from aqueous solutions. METHODS: The nanocomposite-activated carbons were characterized via scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, Brunauer Emmett Teller (BET) and other techniques. Batch equilibrium experiments were conducted in order to investigate the effects of solution pH, adsorbent dosage, initial PFAS concentration and temperature on the removal of PFAS using PAMTAg and CAMTAg. Langmuir and Freundlich adsorption isotherm models were used to analyse the equilibrium data obtained. RESULTS: Maximum adsorption capacities of 454.1 mg/g (0.91 mmol/g) and 321.2 mg/g (0.78 mmol/g) were recorded for perfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA), respectively using CAMTAg. The values recorded for the Gibbs' free energy (ΔG°) for the adsorption of PFOS and PFOA onto PAMTAg and CAMTAg were negative; PFOS (-9.61, -9.99 and - 10.39), PFOA (-8.77, -9.76 and - 10.21) using PAMTAg; and PFOS (-13.70, -12.70 and - 12.37), PFOA (-12.86, -12.21 and - 11.17) using CAMTAg. Therefore, the adsorption processes were spontaneous and feasible. The values recorded for enthalpy (ΔH°) (kJ/mol) for the adsorption of PFOS (-26.15) and PFOA (-35.86) onto CAMTAg were negative, indicating that the adsorption mechanism is exothermic in nature. Positive values were recorded for ΔH° for the adsorption of PFOS (2.32) and PFOA (12.69) onto PAMTAg, indicative of an endothermic adsorption mechanism. Positive entropy (ΔS°) values (0.04 and 0.07) were recorded for PFOS and PFOA using PAMTAg; whereas negative values (-0.04 and - 0.08) were recorded for ΔS° using CAMTAg. A positive ΔS° indicates an increase in randomness of the adsorbate at the solid-solution interface and the reverse is the case for a negative ΔS°. CONCLUSION: The interplay of electrostatic attraction and hydrophobic interactions enabled the removal of PFAS using PAMTAg and CAMTAg. Findings suggest that PAMTAg and CAMTAg are effective for the removal of PFAS from aqueous media and are good alternatives to commercially available activated carbons. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40201-020-00597-3.
Keywords: PFOS; PFOA; Activated carbon; Maize tassel; Silver nanocomposite; Adsorption